أزمة كورونا و متطلبات حماية البيئة في ظل العولمة Corona virus crisis and the environmental protection recommendations under globalization - باهي, سمير; زنودة, منى (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
يهدف البحث للتعرف إلى آثار جائحة فيروس كورونا كوفيد 19 على البيئة العالمية خصوصا في ظل العولمة و ما تطرحه من تحديات داخلية و خارجية. حيث تعتبر جائحة كورونا أحد تجليات العولمة و الانفتاح على الخارج، فتحاول هذه الدراسة التركيز على الآثار التي خلفتها جائحة كورونا على البيئة العالمية في إطار عولمة المخاطر من خلال البحث فيما طرحته من خسائر و تحديات على الصعيدين الوطني و الدولي. The research aims to identify the effects of the Coronavirus Covid 19 pandemic on the global environment, especially under globalization and it’s national and external challenges. This pandemic can be considered as a result of the globalized world. This study attempts to focus on the effects of the Corona-virus pandemic on the global environment in the context of globalizing risks by examining the losses and challenges it presented at the national and international levels.